Prawne i administracyjne podstawy tworzenia systemu militarnego na Śląsku na przykładzie księstwa głogowskiego w czasach habsburskich (1526-1740) = The military, social and economic basis for creating a security system in Silesia on the example of principality of Głogów in Habsburg times (1526-1740) - Kuczer, Jarosław (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In the Habsburg period in Silesia (1526-1740), especially important, was the problem to rebuild the defensive structures of the province. The whole process was an attempt to take over the system by the Czech king, the Roman emperor themselves. The Emperor tried to deprive the Estates of the Realm of any influence on above mentioned area. Since the Middle Ages, the Duchy of Głogów, especially the nobility, held the most of the prerogatives in relation to almost every elements of defense system. It concerned mainly the consent to the collection of taxes in the event of a military threat, until the always too slow permission to participate in campaigns outside the province, and even the compulsion to take out of the possible imprisonment of the Silesian nobles.
Keywords: Śląsk; Księstwo Głogowskie - 16 -18 w.; Habsburgowie; bezpieczeństwo; Silesia; Principality of Głogów; Habsburgs; security